Sequential Inoculation of Native Non-Saccharomyces and Saccharomyces cerevisiae Strains for Wine Making - Padilla, Beatriz; Zulian, Laura; Ferreres, Àngela; Pastor, Rosa; Esteve-Zarzoso, Braulio; Beltran, Gemma; Mas, Albert (Frontiers in Microbiology, 2017)
The use of non-Saccharomyces yeast for wine making is becoming a common trend in many innovative wineries. The application is normally aimed at increasing aromas, glycerol, reducing acidity, and other improvements. This manuscript focuses on the reproduction of the native microbiota from the vineyard in the inoculum. Thus, native selected yeasts (Hanseniaspora uvarum, Metschnikowia pulcherrima, Torulaspora delbrueckii, Starmerella bacillaris species and 3 different strains of Saccharomyces cerevisiae) were inoculated sequentially, or only S. cerevisiae (3 native strains together or one commercial) was used. Inoculations were performed both in laboratory conditions with synthetic must (400 mL) as well as in industrial conditions (2000 kg of grapes) in red winemaking in two different varieties, Grenache and Carignan. The results showed that all the inoculated S. cerevisiae strains were found at the end of the vinifications, and when non-Saccharomyces yeasts were inoculated, they were found in appreciable populations at mid-fermentation. The final wines produced could be clearly differentiated by sensory analysis and were of similar quality, in terms of sensory analysis panelists’ appreciation.